'It Was an Imitashon to be Sure': The Imitation Indian Shawl in Design Reform and Imaginative Fiction. (3rd July 2015) - Choudhury, Suchitra
Abstract : Indian Cashmere shawls were costly accessories in nineteenth-century Britain, and they were 'imitated' in Edinburgh, Norwich and Paisley. This article argues that shawls were at the centre of a key debate within the design reform movement, which viewed imitations as clumsy copies of a perfectly designed textile. It examines Victorian texts such as design reformers' publications and works of fiction, to suggest that their understanding of shawls that imitated Indian designs was linked, in part, to class prejudices. Paisley shawls' stereotyping as an article emblematic of bad taste and a lower-class desire for social mobility was thus not limited to the writings of a small coterie of design reformers, but was found also reflected in works of best-selling writers such as Charles Dickens, Walter Scott and Wilkie Collins.